2015
DOI: 10.1016/j.compchemeng.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Variant and invariant states for chemical reaction systems

Abstract: a b s t r a c tModels of chemical reaction systems can be quite complex as they typically include information regarding the reactions, the inlet and outlet flows, the transfer of species between phases and the transfer of heat. This paper builds on the concept of reaction variants/invariants and proposes a linear transformation that allows viewing a complex nonlinear chemical reaction system via decoupled dynamic variables, each one associated with a particular phenomenon such as a single chemical reaction, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 40 publications
0
61
0
Order By: Relevance
“…When there are at least as many measured species as independent reactions, Rodrigues et al (2015) have shown how to compute the extents by means of a linear transformation. With rank(N)=R, this transformation requires rank(G N T )=R, from which it follows that M ≥ R. If the number of measured species, or more generally the number of measurements, is such that M < R, it is no longer possible to compute all R extents from M measurements without a kinetic model.…”
Section: Computation Of Extents Under Rank-deficient Conditionsmentioning
confidence: 99%
“…When there are at least as many measured species as independent reactions, Rodrigues et al (2015) have shown how to compute the extents by means of a linear transformation. With rank(N)=R, this transformation requires rank(G N T )=R, from which it follows that M ≥ R. If the number of measured species, or more generally the number of measurements, is such that M < R, it is no longer possible to compute all R extents from M measurements without a kinetic model.…”
Section: Computation Of Extents Under Rank-deficient Conditionsmentioning
confidence: 99%
“…, R) depending on the rate r v,i , the manipulated variable q ex , a combination of the inlet flowrates u in , and ω the inverse of the residence time. To be applicable, the transformation T requires that at least R elements of the vector z be measured (Rodrigues et al (2015)). Note that transformations based on…”
Section: Transformation To Reaction-variant Statesmentioning
confidence: 99%
“…A finer separation of the various dynamic effects in both homogeneous and heterogeneous open reaction systems has been proposed by and , and reformulated recently as a linear transformation of the numbers of moles to so-called vessel extents by Rodrigues et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…The matrix P represents the null space of the corresponding structural matrix. Amrhein et al (2010) and Rodrigues et al (2015) have developed a linear transformation for open reaction systems that transforms the numbers of moles n into four contributions, namely, the R extents of reaction x r , the p extents of inlet x in , a dimensionless extent of initial conditions x ic , and the q = S − R − p − 1 invariants x iv that are identically zero. The linear transformation T reads:…”
Section: Conservation Equationsmentioning
confidence: 99%